2018
DOI: 10.1039/c8py00198g
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of crystallization rates in miscible block copolymers of poly(lactide)-block-poly(2-isopropyl-2-oxazoline)

Abstract: a Miscible block copolymers (BCPs) are rarely studied. When one or both components of such BCPs are semi-crystalline polymers, strong effects on the crystallization behavior can be expected. We present a study of 18 miscible BCPs comprised of poly(lactide) (PLLA, semi-crystalline and PDLLA, amorphous) and poly(2-isopropyl-2-oxazoline) (PiPOx, semi-crystalline) with PiPOx volume fractions of 0.14 < ϕ PiPOx < 0.82. All BCPs exhibit a single glass transition and form a homogeneous melt. Mixing has a plasticizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…When a solvent-selective BCP comprises two blocks miscible in the bulk phase, the attraction between the two blocks becomes an important parameter to consider when assessing its assembly in a selective solvent. We recently reported that poly­( l -lactide)- b- poly­(2-isopropyl-2-oxazoline) (PiPOx - b - PLLA) BCPs are miscible in the bulk . Dipolar interactions of the carbonyl groups of the PiPOx and PLA blocks are responsible for the miscibility, as confirmed experimentally in the FTIR spectra of PiPOx- b -PLLA, which presents shifts of the PiPOx carbonyl-stretching vibrations as a function of the PLLA content.…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…When a solvent-selective BCP comprises two blocks miscible in the bulk phase, the attraction between the two blocks becomes an important parameter to consider when assessing its assembly in a selective solvent. We recently reported that poly­( l -lactide)- b- poly­(2-isopropyl-2-oxazoline) (PiPOx - b - PLLA) BCPs are miscible in the bulk . Dipolar interactions of the carbonyl groups of the PiPOx and PLA blocks are responsible for the miscibility, as confirmed experimentally in the FTIR spectra of PiPOx- b -PLLA, which presents shifts of the PiPOx carbonyl-stretching vibrations as a function of the PLLA content.…”
Section: Introductionmentioning
confidence: 62%
“…We recently reported that poly( l -lactide)- b- poly(2-isopropyl-2-oxazoline) (PiPOx - b - PLLA) BCPs are miscible in the bulk. 3 Dipolar interactions of the carbonyl groups of the PiPOx and PLA blocks are responsible for the miscibility, as confirmed experimentally in the FTIR spectra of PiPOx- b -PLLA, which presents shifts of the PiPOx carbonyl-stretching vibrations as a function of the PLLA content. The close values of the solubility parameters of PiPOx and PLA (δ PiPOx : 24.0 J 0.5 /cm 1.5 ; δ PLA : 22.7 J 0.5 /cm 1.5 ) calculated by the method of Fedors 4 support the experimental observations.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations